THE EFFECT OF WORK PLACEMENT MEDIATED BY WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE PUBLIC WORKS AND SPATIAL PLANNING OFFICE OF KONAWE ISLANDS REGENCY - Andriawan, Andre Eka; Muthalib, Abdul Azis; Hakim, Abdul (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study aims to find out and analyze  the influence  of work placement mediated by work motivation on the performance of employees at  the Public Works and Spatial Planning Office of Konawe Islands Regency. The determination of the number of samples in this study is by using the census method, namely the number of samples taken from the total population of 56 employees. The data analysis technique in this study uses Partial Least Square (PLS).  Based on the results of the study, it can be concluded that (1) Job placement has a positive and significant effect on  the work motivation  of employees at the Public Works and Spatial Planning Office of Konawe Islands Regency;(2) Work placement has a positive and significant effect on employee performance at the Public Works and Spatial Planning Office of Konawe Islands Regency;     (3) Work motivation has a positive and significant effect on employee performance at the Public Works and Spatial Planning Office of Konawe Islands Regency; (4) Job placement has a positive and significant effect on employee performance through employee work motivation at the Public Works and Spatial Planning Office of Konawe Islands Regency.